2006
DOI: 10.1007/s00125-006-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

High glucose and homocysteine synergistically affect the metalloproteinases–tissue inhibitors of metalloproteinases pattern, but not TGFB expression, in human fibroblasts

Abstract: Aims/hypothesis Atherosclerosis is particularly aggressive in patients with diabetes. Hyperhomocysteinaemia causes oxidative stress and cytokine secretion: its atherogenic effect is mediated by an enhanced inflammatory response. Matrix metalloproteinases (MMPs) regulate extracellular matrix degradation and remodelling, and contribute to the vulnerability of the atherosclerotic lesion. Fibroblasts contribute to collagen biosynthesis and participate in plaque remodelling via expression and release of MMP2 and MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Contrary to earlier findings [28], exchanging glucose levels failed to significantly effect TGF-β expression in either db/db or db/wt cells. Similar findings by Solini et al showed TGF-β mRNA transcript levels were not changed by altering glucose levels in a human fibroblast culture model system [43]. PAI-1 is another potent, biochemical stimulus capable of contributing to a profibrotic environment by inactivating proMMPs [44].…”
Section: Discussionsupporting
confidence: 61%
“…Contrary to earlier findings [28], exchanging glucose levels failed to significantly effect TGF-β expression in either db/db or db/wt cells. Similar findings by Solini et al showed TGF-β mRNA transcript levels were not changed by altering glucose levels in a human fibroblast culture model system [43]. PAI-1 is another potent, biochemical stimulus capable of contributing to a profibrotic environment by inactivating proMMPs [44].…”
Section: Discussionsupporting
confidence: 61%
“…[8][9][10] Determination of MMP9 mRNA [11] MMP9 mRNA levels were determined by realtime PCR. GAPDH was used as the internal control (Table 1) Determination of MMP9 protein MMP9 protein was measured by ELISA assay.…”
Section: Cell and Reagentsmentioning
confidence: 99%
“…Thus, TIMPs regulate ECM by inhibiting MMPs. HHcy induces MMP-2, -9 [13] and also modulates TIMPs [15] to promote matrix accumulation [16]; however, whether a similar mechanism is involved in Ang II-induced kidney remodeling has not been reported.…”
Section: Introductionmentioning
confidence: 99%